The Growth Characteristics of Patients with Noonan Syndrome: Results of Three Years of Growth Hormone Treatment: A Nationwide Multicenter Study - (:unkn) unknown (My University, 2016)
0

Objective: Noonan syndrome (NS) is a multisystem disorder, and short stature is its most striking manifestation. Optimal growth hormone (GH) treatment for NS is still controversial. In this study, using a nationwide registration system, we aimed to evaluate the growth characteristics and the clinical features of NS patients in Turkey and their growth response to GH treatment. Methods: Children and adolescents with a diagnosis of NS were included inthe study. Laboratory assessment including standard GH stimulation test results were evaluated. Height increment of patients with or without GH treatment were analyzed after three years of therapy.This study aimed to descript the characteristics of Noonan syndrome at a national level.Information about the clinical characteristics, especially in growth parameters of NS patients at national level is scarce. In this study, using a nationwide registration system, we aimed to evaluate the growth characteristics, clinical features, and response to GH treatment of NS patients in Turkey.MethodsIn this study, we retrospectively analysed the data of 124 children and adolescents with NS who were being followed in 20 centers in Turkey. Study approval was given by the Ankara University Ethics Committee. A nation-wide Results: A total of 124 NS patients from different centers were entered in the webbased system. Short stature and typical face appearance were the most frequently encountered diagnostic features of our patients. Of the 84 patients who were followed long-term, 47 hadreceived recombinant human GH (rhGH). In this group of 47 patients, height standard deviation score (HSDS) increased from -3.62±1.14 to -2.85±0.96 after three years of therapy, indicating significant differences from the patients who did not receive GH treatment. PTPN11 gene was analyzed in 61 patients, and 64% of these patients were found to have a mutation. HSDS at admission was similar in patients with or without PTPN11 gene mutation.Conclusion: A diagnosis of NS should be kept in mind in all patients with short stature showing systemic clinical findings. GH therapy is effective for improvement of short stature especially in the first two years of treatment. Further studies are needed for optimisation of GH therapy and evaluation of final height data in NS patients.
Keywords: Endokrinoloji ve Metabolizma; Pediatri